High DHEAS/free testosterone ratio is related to better metabolic parameters in women with PCOS - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2015)
Aims: To demonstrate the effects of DHEAS/free testosterone (DHEAS/FT) ratio on metabolic parameters in women with and without polycystic ovary syndrome (PCOS). Methods: The data of 91 women with PCOS and 66 women in the control group were collected retrospectively. Results: DHEAS/FT of the control group was higher than that of PCOS group (684.93 +/- 300.54 to 517.2 +/- 300.8, p<0.001). DHEAS/FT correlated with BMI (r=0.352, p=0.001), WHR (r=0.371, p=0.0219), LDL (r=0.227, p=0.031), HOMA-IR (r=0.36, p=0.001) and FAI (r=0.639, p=0.001) negatively and with HDL (r=0.344, p=0.001) and SHBG (r=-0.646, p=0.001) positively. In the control group, DHEAS/FT correlated with BMI (r=0.334, p=0.007), CRP (r=0.297, p=0.016) and FAI (r=0.399, p=0.01) negatively. Conclusions: High DHEAS/FT ratios are related to a better metabolic phenotype in women with PCOS and low levels can be used to detect women with PCOS that have a higher risk of metabolic problems.
Keywords: DHEAS; free testosterone; metabolism; polycystic ovary syndrome; POLYCYSTIC-OVARY-SYNDROME; ADRENAL ANDROGEN SECRETION; DEHYDROEPIANDROSTERONE-SULFATE; BODY-COMPOSITION; FAT DISTRIBUTION; METFORMIN; OBESITY; ABNORMALITIES; RISK; MEN